Long-term Outcome of Implantable Cardioverter/Defibrillator Lead Failure - Davidsson, Gustav Arnar (JAMA Intern Med, 2019)
This study compares outcomes of a recalled implantable cardioverter/defibrillator lead with a control lead in individuals in Iceland.